2011
DOI: 10.1002/eco.259
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic review of feedbacks and drivers of shrub encroachment in arid grasslands

Abstract: Many arid grasslands around the world are affected by woody plant encroachment and by the replacement of a relatively continuous grass cover with shrub patches bordered by bare soil. This shift in plant community composition is often abrupt in space and time, suggesting that it is likely sustained by positive feedbacks between vegetation and environmental conditions (e.g. resource availability) or disturbance regime (e.g. fire or freeze). These feedbacks amplify the effects of drivers of shrub encroachment, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
298
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 359 publications
(313 citation statements)
references
References 104 publications
(157 reference statements)
8
298
1
6
Order By: Relevance
“…Thereby, it is generally assumed that the living grasses use their superior competitive abilities (Cech, Edwards, & Olde Venterink, 2010) to maintain their dominance by suppressing the germination, reducing the growth, and thus regulating the establishment of trees and other competing species (Bond, 2008; D’Odorico, Okin, & Bestelmeyer, 2012; Sankaran, Ratnam, & Hanan, 2004). However, some studies contradict these findings and found, for example, seedlings of Acacia mellifera to grow and establish even when growing within grass tussocks (Joubert, Smit, & Hoffman, 2012; Rothauge, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, it is generally assumed that the living grasses use their superior competitive abilities (Cech, Edwards, & Olde Venterink, 2010) to maintain their dominance by suppressing the germination, reducing the growth, and thus regulating the establishment of trees and other competing species (Bond, 2008; D’Odorico, Okin, & Bestelmeyer, 2012; Sankaran, Ratnam, & Hanan, 2004). However, some studies contradict these findings and found, for example, seedlings of Acacia mellifera to grow and establish even when growing within grass tussocks (Joubert, Smit, & Hoffman, 2012; Rothauge, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The high aeolian sediment transport in the natural shrub plot has resulted in a notable growth of shrub islands under the mesquites, i.e., from an aveage width of 1.5 m in 2005 [Li et al, 2008] to 3.3 m in 2015. The slow formation of soil mounds under the artificial shrubs may be the net consequence of a number of factors: 1) the aeolian sediment flux was low in the artificial shrub experimental sites, 2) the directional movement of soil particles from under shrub canopy to shrub interspace may also partially counteract the accumulation of soil particles under the shrub, and 3) very importantly, the disconnection of the positive feedback to the growth of shrub dunes and the development of fertile islands that is essential in the natural shrub dune systems [Schlesinger et al, 1990;D'Odorico et al, 2012]. With regard to vegetation structure, Raupach et al [2001] concluded that the efficiency of entrapment of windborne particles was related to optical porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Fertile islands have been documented in desert habitats on all continents, but they are particularly well described in the desert grassland of the southwestern United States [e.g., Schlesinger and Pilmanis, 1998;Okin and Gillette, 2001;Shade and Hobbie, 2005;Thompson et al, 2005;Ravi et al, 2011;Allington and Valone, 2014]. The conversion of perennial grasslands into desert shrublands and the consequent redistribution of soil resources have important implications for local pastoral economics, regional and global climate, biogeochemical cycles, biodiversity, and human health [Schlesinger et al, 1990;Jackson et al, 2002;Eldridge et al, 2011;D'Odorico et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, for more than 20 years, shrub encroachment into rangelands has been recognized as a desertification indicator [4][5][6][7][8][9]. However, some alternative viewpoints have emerged recently [10][11][12][13][14]. In the rangelands of Inner Mongolia, China, shrub encroachment studies have been undertaken in recent years.…”
Section: Introductionmentioning
confidence: 99%